The distribution, abundance, and community perception of Proboscis Monkey (Nasalis larvatus) in Limbang Mangrove National Park, Sarawak - Ahmad Fitri, Aziz; Mohd Azlan, Jayasilan (Malaysian Nature Society, 2022)
The Proboscis Monkey is endemic to Borneo, where the species is widely distributed in mangroves and estuarine habitat. Sensitive to disturbance, and with a declining population listed by IUCN as ‘Endangered’, protective legislation is generally in place. Treated as an ‘iconic’ species for tourism in Sarawak, several mangrove areas have been protected for conservation of the species. Limbang Mangrove National Park is one such place but, with an estimated population of 44 individuals in 2019, had become a critical site. A new survey of 11 boat trips covering 223.59 km of mangrove riverbank in Limbang Mangrove National Park and adjoining estuaries recorded 236 individuals in 34 groups. The estimated population density was 1.03-1.78 individuals/km2, and 0.15-0.25 groups/km2. Proboscis Monkeys were evenly distributed within the National Park boundaries, but concentrated at the centre of the Park. A questionnaire survey of local communities found that more than 50% of respondents supported conservation of this species. Based on the Boosted Regression Tree analysis, locality and income of the respondents were the most influential factors that influenced their perception towards the conservation of Proboscis Monkey in Limbang Mangrove National Park. We conclude that conservation and sustainable ecotourism activities regarding Proboscis Monkeys in Limbang Mangrove National Park should give priority to carfeful planning, taking into consideration the long-term existence of this totally protected species.